Opinions on the Future of Clinical Pig Kidney Xenotransplantation - Georg A. Böhmig; Matthias Diebold; Matthias Diebold; Klemens Budde (Transplant International)
Based on promising results obtained in primate models, pioneers in the US have now started to explore the new frontier of genetically-edited pig-to-human transplantation. The recent transition of xenotransplantation into clinical medicine has included transplants in brain-dead subjects and the compassionate use of xenotransplants in living recipients without options for allotransplantation. While the barrier of hyperacute rejection seems to be successfully overcome by gene editing of donor pigs, the occurrence of accelerated rejection could pose significant limitations to the success of the procedure. Ultimately, the establishment of efficient and safe strategies to overcome immunologic barriers will, among other critical factors, such as potential xenozoonotic disease transmission or physiological differences, determine whether and for which indications xenotransplantation will be viable. Considering preliminary outcomes of compassionate use xenotransplantions, which may raise questions about how faithfully data from non-human primate models translate into human outcomes, further research in decedents may be necessary before proceeding with additional clinical transplants. Looking ahead, designing systematic trials in xenotransplantation, including the definition of acceptable eligibility criteria for such high-risk transplants, will be an immense challenge, especially in kidney transplantation, where dialysis provides an effective alternative to transplantation in most cases.